The Effect of Hearing Loss on Localization of Amplitude-Panned and Physical Sources - Ellis, Gregory M.; Souza, Pamela E. (Journal of the American Academy of Audiology, 2020)
Background Clinics are increasingly turning toward using virtual environments to demonstrate and validate hearing aid fittings in “realistic” listening situations before the patient leaves the clinic. One of the most cost-effective and straightforward ways to create such an environment is through the use of a small speaker array and amplitude panning. Amplitude panning is a signal playback method used to change the perceived location of a source by changing the level of two or more loudspeakers. The perceptual consequences (i.e., perceived source width and location) of amplitude panning have been well-documented for listeners with normal hearing but not for listeners with hearing impairment.Purpose The purpose of this study was to examine the perceptual consequences of amplitude panning for listeners with hearing statuses from normal hearing through moderate sensorineural hearing losses.Research Design Listeners performed a localization task. Sound sources were broadband 4 Hz amplitude-modulated white noise bursts. Thirty-nine sources (14 physical) were produced by either physical loudspeakers or via amplitude panning. Listeners completed a training block of 39 trials (one for each source) before completing three test blocks of 39 trials each. Source production method was randomized within block.Study Sample Twenty-seven adult listeners (mean age 52.79, standard deviation 27.36, 10 males, 17 females) with hearing ranging from within normal limits to moderate bilateral sensorineural hearing loss participated in the study. Listeners were recruited from a laboratory database of listeners that consented to being informed about available studies.Data Collection and Analysis Listeners indicated the perceived source location via touch screen. Outcome variables were azimuth error, elevation error, and total angular error (Euclidean distance in degrees between perceived and correct location). Listeners' pure-tone averages (PTAs) were calculated and used in mixed-effects models along with source type and the interaction between source type and PTA as predictors. Subject was included as a random variable.Results Significant interactions between PTA and source production method were observed for total and elevation errors. Listeners with higher PTAs (i.e., worse hearing) did not localize physical and panned sources differently whereas listeners with lower PTAs (i.e., better hearing) did. No interaction was observed for azimuth errors; however, there was a significant main effect of PTA.Conclusion As hearing impairment becomes more severe, listeners localize physical and panned sources with similar errors. Because physical and panned sources are not localized differently by adults with hearing loss, amplitude panning could be an appropriate method for constructing virtual environments for these listeners.
Keywords: hearing loss; auditory perception; spatial processing